Post-postbiological evolution? - Ćirković, Milan M. (Futures, 2018)
It has already become a commonplace to discuss postbiological evolution in various contexts of futures studies, bioethics, cognitive sciences, philosophical anthropology, or even economics and SETI studies. The assumption is that technological/cultural evolution will soon entirely substitute for the biological processes which underlie human existence – and, by analogy, the existence of other independently evolved intelligent beings, if any. Various modes of postbiological evolution of humans have been envisioned in both fictional and discursive contexts (uploading, cyborgization, technological singularity, etc.). Little thought has been devoted so far to the question whether these postbiological modes are truly final in both logical and conceptual terms. What lies beyond the postbiological realm? Clearly, only a few radical speculations on the topic can be offered. In this paper, it is argued that in a sufficiently broad subset of scenarios for postbiological evolution there will be a kind of reverse trend: the one of reintegration with the (astro)biological universe, by that point understood in a much wider and more inclusive sense. The argument for such reintegration could be understood through the metaphor of expanding Klein bottle as a symbolic image of the post-postbiological evolutionary trajectories. This kind of trajectory will lead to the state in which products of culture are indistinguishable from the natural environment, suggesting practical consequences for our SETI efforts.